Students as researchers for promoting school improvement and inclusion: a review of studies. Issue 8 (3rd July 2022) - Sandoval, Marta; Messiou, Kyriaki
ABSTRACT: This paper comprises a review of studies that employ students as researchers/co-researchers approaches from 2000 to 2018, with a focus on school improvement and inclusion. The study is original since it focuses exclusively on the idea of students taking the role of researchers/co-researchers, instead of focusing on the broader notion of student voice that other reviews have explored previously. The results highlight the different school improvement areas that are explored and the various stages that have been followed in the studies in order to involve students. Through this analysis, we focus our discussion on issues that need to be considered when using such approaches. Overall, we argue that despite the inherent challenges that such approaches entail, students as researchers/co-researchers can be a powerful way for improving schools and promoting inclusion.